SAT0282 Presentation Patterns in a Cohort of Patients with Psoriatic Arthritis. (23rd January 2014) - Zisman, D.; Elias, M.; Eder, L.; Novofastovski, I.; Feld, J.; Mader, R.
Abstract : Background: Arthritis is estimated to precede skin psoriasis in approximately 15% of psoriatic arthritis patients (PsA) (1 ). However this data is based on studies published prior to the development of the Classification for Psoriatic Arthritis (CASPAR) criteria(2 ). Objectives: The aim of this study is to characterize clinical, laboratory and radiological features that distinguish PsA patients diagnosed based on CASPAR criteria, who present with arthritis before psoriasis from those who develop either concomitant skin or joint manifestations or arthritis following psoriasis. Methods: A retrospective cohort study of patients with PsA fulfilling the CASPAR criteria and followed in two rheumatology clinics was conducted. All charts were reviewed and clinical, laboratory and radiological manifestations at the first rheumatology evaluation were analyzed. Patients were divided into 3 groups according to the relation between the onset of the cutaneous psoriasis and arthritis: Group A (skin before joints), Group B (joints before skin), and Group C (simultaneous presentation). Analysis of variance and t-test were used to compare continuous variables. A Chi square test was used for categorical variables. Results: Overall 160 patients were included: 121(75.6%) in Group A, 12 (7.5%) in Group B and 27 (16.9%) in Group C. Of these, 63 (39.4%) were males. Their mean age was 55.2±14.4 years. The mean age at onset of psoriasis and PsA were 39.7±16.3 and 48.3±14.3, respectively. No statistically significant difference across the groups with respect to age, gender, ethnicity and family history of psoriasis was observed. A polyarthritis pattern was observed in 81 (68.1%), 11 (91.7%), and 22 (81.5%) patients, respectively (p=0.11); oligoarthritis in 31 (26.5%), 1 (9.1%), and 4 (16%) patients, respectively (p=0.26); spinal involvement in 22(18.3%), 4 (33.3%), and 4 (14.8%) patients, respectively (p=0.37); and distal interphalangeal joint involvement in 16 (13.3%), 3 (27.3%) and 0 (0%) patients, respectively (p=0.04). No statistically significant differences were noted in the prevalence of entheseal, nail and dactylitis involvement. Radiographic studies revealed bone erosions in 28 (28%), 4 (33.3%) and 5 (25%) patients, respectively; radiographic sacroiliitis in 20 (20%), 3 (25%) and 3 (15.8%), patients, respectively; and new bone formation in 9 (8/9%), 1(8/3%) and 1(5.6%) patients, respectively, with no statistically significant differences. No statistically significant differences were noted in c-reactive protein levels, the prevalence of rheumatic factor and antinuclear antibody positivity. Conclusions: A lower prevalence of PsA (7.5%) preceding skin manifestation was observed in our study using stringent CASPAR criteria compared to previous data published. No statistically significant differences in clinical, laboratory and radiological manifestations were noted across the analyzed groups. Polyarthritis is the most common pattern of PsA presentation. References: Gladman DD, Shuckett R, Russeii ML, et al: Psoriatic arthritis-an analysis of 220 patients. Q J Med1987; 62:127-141. Taylor W, Gladman D, Helliwell P, et al: Classification criteria for psoriatic arthritis: development of new criteria from a large international study. Arthritis Rheum. 2006; 54:2665-73. Disclosure of Interest: None Declared